A Study of the Boom and Bust Cycles of the United States Housing Market from 2000 to 2010 - Liu, Wei (Université d'Ottawa | University of Ottawa, 2011)
This paper looks at the evolution of the housing market in the US from 2000 to 2010. This period is characterized by interesting and dramatic boom and bust cycles in the housing market. Data from the fifty states and the District of Columbia are used to s